Would You Prescribe Mobile Health Apps for Heart Failure Self-care? An Integrated Review of Commercially Available Mobile Technology for Heart Failure Patients - Andrea Mortara; Lucia Vaira; Vittorio Palmieri; Massimo Iacoviello; Ilaria Battistoni; Attilio Iacovoni; Francesca Macera; Daniele Pasqualucci; Mario Bochicchio; Renata De Maria (Cardiac Failure Review)
Treatment of chronic diseases, such as heart failure, requires complex protocols based on early diagnosis; self-monitoring of symptoms, vital signs and physical activity; regular medication intake; and education of patients and caregivers about relevant aspects of the disease. Smartphones and mobile health applications could be very helpful in improving the efficacy of such protocols, but several barriers make it difficult to fully exploit their technological potential and produce clear clinical evidence of their effectiveness. App suppliers do not help users distinguish between useless/dangerous apps and valid solutions. The latter are few and often characterised by rapid obsolescence, lack of interactivity and lack of authoritative information. Systematic reviews can help physicians and researchers find and assess the ‘best candidate solutions’ in a repeatable manner and pave the way for well-grounded and fruitful discussion on their clinical effectiveness. To this purpose, the authors assess 10 apps for heart failure self-care using the Intercontinental Marketing Statistics score and other criteria, discuss the clinical effectiveness of existing solutions and identify barriers to their use in practice and drivers for change.